Nurse shortage or nursing shortage: have we missed the real problem? - Bower FL; McCullough C (Nursing Economic$)
Many strategies have been used to solve the nurse shortage. The shortage of nurses has in many ways alerted us to the need to provide safe and efficient care using the latest technology. Nursing needs to adopt, refine, and use this technology so the impact of the nursing shortage is just another statistic and not a disruptive and costly threat to the public.